2022
DOI: 10.3390/ijerph191610156
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of International Nonproprietary Names Integration on Prescribing Reimbursement Medicines for Arterial Hypertension and Analysis of Medication Errors in Latvia

Abstract: The use of international nonproprietary names (INNs) has been mandatory for prescriptions of state-reimbursed drugs in Latvia since 1 April 2020. In a retrospective analysis, we aimed to examine the impact of the new regulation on changes in the prescribing and dispensing practice of antihypertensive agents with an example of bisoprolol or/and perindopril and their combinations. All state-reimbursed bisoprolol and/or perindopril prescriptions for arterial hypertension were evaluated in two time periods: 1 Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…It has been proven that providing recommendations is insufficient to bring about substantial changes in behaviour or practices. Regulation changes are necessary [45]. This study's results also indicate a significant impact on practice by the mandatory use of electronic prescribing systems from 2018 and INN from 2020 for reimbursement purposes [46,47].…”
Section: Discussionmentioning
confidence: 85%
“…It has been proven that providing recommendations is insufficient to bring about substantial changes in behaviour or practices. Regulation changes are necessary [45]. This study's results also indicate a significant impact on practice by the mandatory use of electronic prescribing systems from 2018 and INN from 2020 for reimbursement purposes [46,47].…”
Section: Discussionmentioning
confidence: 85%
“…For example, they were adopted in Australia in 2016 7 and in Latvia in April 2020. 8 A before-and-after study in Latvia showed that after the adoption of INNs, their use in prescriptions for bisoprolol and/or perindopril increased from 2.1% to 92.3% and the rate of medication errors fell from 0.81% to 0.39%.…”
Section: A Final Thoughtmentioning
confidence: 99%